Análise de elementos da gestão do conhecimento nos projetos de reformulação organizacional da Caixa Econômica Federal. - Endres, Celso (2003)
Within a environment of great changes, one believes that the way how a company produces and transmits the knowledge is essencial to its continuity and it has been under the Knowledge Management point of view that this work analyses the organizational reformulation projects in the Agencias da Caixa Economica Federal, started from the Project 500 and followed by the Net of Processes and the Customers Segmentation Strategic Model. To reach the proposed goal, it has been taken from the literature about the study topic, dimensions and elements enabling a tool structure of analysis to identify possible effective practices of Knowledge Management in the company through methodology systematization applied and reported data analysis. This study analyse how the elements of Knowledge Management are in the innovations occurred in the enterprise during the last years. One may realize that the goal has been achieved and the identified elements were classified as string, moderate and weak by its performance and served of reference to propositions of improvements of knowledge use in the organization. This has been the main contribution of this study for the company with the guidelines of how to generate, codify and transfer the tacit knowledge into explicit one. The former in the researched company is predominant and of high quality, developing a necessity of a trained managerial body with defined attributions and responsibilities to lead the knowledge use in the company through Technology, Processes and People.